2015
DOI: 10.1080/19491034.2015.1075111
|View full text |Cite
|
Sign up to set email alerts
|

Localized movement and morphology of UBF1-positive nucleolar regions are changed by γ-irradiation in G2 phase of the cell cycle

Abstract: (2015) Localized movement and morphology of UBF1-positive nucleolar regions are changed by γ-irradiation in G2 phase of the cell cycle, Nucleus, 6:4, 301-313, DOI: 10.1080/19491034.2015 To link to this article: https://doi.org/10. 1080/19491034.2015 Abbreviations: 53BP1, p53-binding protein; ACT-D, actinomycin D; ATM, ataxia telangiectasia mutated; ATR, ATM and Rad3-related protein; AR, area ratio (area of nucleolus/area of nucleus); BrdU, 5-bromo-2 0 -deoxy-uridine; BER, base excision repair; CBs, Cajal bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…FRAP analyses were then performed 90–120 min after γ‐irradiation. Since UVA but not 5Gy of γ‐rays induced apoptotic fragmentation of lamin B, we concluded that γ‐irradiation induced DNA repair‐related foci but not apoptotic processes (Sorokin et al., ). Similar irradiation conditions we used here.…”
Section: Methodsmentioning
confidence: 85%
“…FRAP analyses were then performed 90–120 min after γ‐irradiation. Since UVA but not 5Gy of γ‐rays induced apoptotic fragmentation of lamin B, we concluded that γ‐irradiation induced DNA repair‐related foci but not apoptotic processes (Sorokin et al., ). Similar irradiation conditions we used here.…”
Section: Methodsmentioning
confidence: 85%
“…This response of nucleolus to cellular stress has been known for decades. 17,40,41 Nucleolar reorganization is often studied by ActD exposure for a short period of time. This produces NCs, most likely as a consequence of transcriptional silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Together, FRAP, time-lapse microscopy, and single-particle tracking analyses represent a valuable biophysical approach for studying the dynamic properties of DNA repair proteins [60,6366]. These experimental tools, which are useful for live cell studies, are essential for understanding the functional properties and hierarchical binding of repair proteins to damaged DNA.…”
Section: Introductionmentioning
confidence: 99%